R&D Heterogeneity and Its Implications for Growth - Sigurd Mølster Galaasen; Alfonso Irarrazabal (Norges Bank, 2016)
This paper quantifies the determinants of heterogeneity in R&D investment and its implications for growth. Using a panel of Norwegian manufacturing firms we document a negative correlation between R&D intensity and firm size, driven mainly by small firms with high R&D intensity. We estimate a Schumpeterian growth model with heterogeneous firms, that differ with respect to innovation efficiency. The estimated model fits the shape of the R&D investment distribution as well as the negative correlation between R&D intensity and firm size. A larger selection effect contribution to aggregate growth is found when we include R&D moments in the estimation. Finally, we study the link between firm heterogeneity and R&D subsidies, and show that the growth effects of subsidies depend crucially on how the policy influences the equilibrium distribution of firms.
hdl:11250/2495713
Keywords: L11; O3; O4; 330; R&D; heterogeneous firms; subsidies; growth